The Perils of Transparency in Bureaucracies - Gavazza, Alessandro; Lizzeri, Alessandro (American Economic Review, 2007)
Many countries have recently enacted or proposed reforms aimed at increasing citizens’ information on the quality of some public sector services. Disclosure of schools’and teachers’ quality is the case that has generated the biggest public debate. In the US, the No Child Left Behind Act (NCLB) requires learning progress to be measured for every child and results from students’tests be made available in annual report cards, so that parents can evaluate schools’ performances. Similar reforms have also been proposed for many other public services. In the UK, legislation introduced in the year 2000 now requires that the performance of each Local Government is reviewed and made public with regards to provision of services such as …re, police, housing, social services and education, but also like the condition of roads, the average time taken to remove ‡y-tips and the amount of household waste recycled. 1 By and large, most of these reforms have been opposed by the public sector employees a¤ected. In the US, the largest teachers union- the National Education Association- spent more than $8 million in an e¤ort to derail NCLB. In the UK, public service unions greeted reforms with increased scepticism and ultimately hostility. More generally, it is di ¢ cult to …nd groups of public sector workers or trade unions lobbying the government to disclose more information about quality. Moreover, in contrast with the private sector, it is much less common to see even the highest quality providers (hospitals, schools,....) trying to